Representing WSDL with extended UML - de Castro, Valeria; Marcos, Esperanza; Vela, Belén (Revista Colombiana de Computación, 2004)
Web services are emerging to provide a systematic and extensible framework for interactions of applications, built on existing Web protocols and based on open XML standards. In spite of the existence of several middleware platforms that support Web service development, the lack of a solid methodological base for the development of Web services, as well as service-oriented applications, give rise to the need of methods or modeling techniques that guarantee the quality in the development of this kind of applications. Keywords: UML extension, WSDL, Web Service Modeling, Web Information Systems.